Overview about the localization of nanoparticles in tissue and cellular context by different imaging techniques - Anja Ostrowski; Daniel Nordmeyer; Alexander Boreham; Cornelia Holzhausen; Lars Mundhenk; Christina Graf; Martina C. Meinke; Annika Vogt; Sabrina Hadam; Jürgen Lademann; Eckart Rühl; Ulrike Alexiev; et al. (Beilstein Journal of Nanotechnology, 2015)
The increasing interest and recent developments in nanotechnology pose previously unparalleled challenges in understanding the effects of nanoparticles on living tissues. Despite significant progress in in vitro cell and tissue culture technologies, observations on particle distribution and tissue responses in whole organisms are still indispensable. In addition to a thorough understanding of complex tissue responses which is the domain of expert pathologists, the localization of particles at their sites of interaction with living structures is essential to complete the picture. In this review we will describe and compare different imaging techniques for localizing inorganic as well as organic nanoparticles in tissues, cells and subcellular compartments. The visualization techniques include well-established methods, such as standard light, fluorescence, transmission electron and scanning electron microscopy as well as more recent developments, such as light and electron microscopic autoradiography, fluorescence lifetime imaging, spectral imaging and linear unmixing, superresolution structured illumination, Raman microspectroscopy and X-ray microscopy. Importantly, all methodologies described allow for the simultaneous visualization of nanoparticles and evaluation of cell and tissue changes that are of prime interest for toxicopathologic studies. However, the different approaches vary in terms of applicability for specific particles, sensitivity, optical resolution, technical requirements and thus availability, and effects of labeling on particle properties. Specific bottle necks of each technology are discussed in detail. Interpretation of particle localization data from any of these techniques should therefore respect their specific merits and limitations as no single approach combines all desired properties.